TANGGUNG JAWAB ORANG TUA DALAM PENDIDIKAN MORAL ANAK - Tibo, Paulinus (IN VERITATE LUX, 2020)
Moral education is an important point in the process of forming human personality. A human being is said to be a moral person if in life he has affective/moral intelligence. A person's knowledge of morals is an integral and inseparable part for every Catholic. Christian moral values ​​are the main foundation in the family education process given by parents to children. So parents as the main educators apply knowledge, skills and Christian moral attitudes. In the data collection process the author conducted research using a qualitative approach with observation, interview and documentation techniques for Catholic families in the St. Peter and Paul Parish, Kabanjahe. The results found were that parents were not fully aware of their responsibilities as parents in moral education in the family. So that children in their daily lives do not emit correct Christian moral attitudes